Influence of inlet-nozzle and outlet-diffuser mounted in the plate-shape reactor on PEMFC net power output and methanol steam reforming performance. (1st October 2022) - Perng, Shiang-Wuu; Wu, Horng-Wen
Graphical abstract: Highlights: We promote performance of a plate-shape MSR to acquire greater PEMFC net power. We study divergent ratio, outlet-diffuser length, temperature on PEMFC net power. The innovative reformer creates higher methanol conversion and hydrogen production. Inlet-nozzle and outlet-diffuser aids mixing and reacting past the reactor channel. The MSR increases hydrogen yield up to 85.70 % or PEMFC net power up to 20.39 %. Abstract: A proton exchange membrane fuel cell (PEMFC) fueled from a plate-shape reactor under steam reforming of methanol is believed to be an optimistic minute power source. This numerical study explores the conversion efficacy of a plate methanol steam reformer (MSR) with an inlet-nozzle and an outlet-diffuser. Considering various convergent ratios and lengths of inlet-nozzle examines the conversion quality of MSR and evaluates PEMFC net power output changing divergent ratio ( λ d ) and length of outlet-diffuser (Ld ) at different wall-heated temperatures (Twall ). The divergent ratio is the reciprocal of convergent ratio. The results depict that the application of inlet-nozzle and outlet-diffuser to a plate reactor significantly enhances the methanol conversion of MSR and PEMFC net output power. Compared to the common reactor without nozzle and diffuser, the innovative reactor with the inlet-nozzle and outlet-diffuser of λ d  = 4.0, and Ld  = 7.5 mm creates the best improvement of the methanol conversion about 21.04 % and the hydrogen gain about 85.66 % at Twall  = 250 °C. Furthermore, the other novel reactor with the inlet-nozzle and outlet-diffuser of λ d  = 4.0, and Ld  = 10.0 mm generates the greatest rise of 20.39 % in PEMFC net output power at Twall  = 250 °C with the permissible CO emission.